A literature review of methods to detect fabricated survey data - Bredl, Sebastian; Storfinger, Nina; Menold, Natalja; Justus Liebig University Giessen (My University, 2011)
This paper reviews literature dealing with the issue of detecting interviewers who falsify survey data. The most reliable method of detecting falsifiers is through face-to-face reinterviewing of survey participants. However, only a limited number of participants can usually be reinterviewed. A review of the present literature clearly indicates that reinterviewing is more effective if the reinterview sample is put together according to some indicators that might be based on metadata, survey data or interviewer characteristics. We examine existing literature with regard to the suitability of different types of indicators that have been used in this context.
Keywords: Interviewer falsification; quality control of survey data; reinterview; ddc:300